Effect of Oil on the Electrodes of the Low-Carbon Steel Welding Using DCSP Polarity in Terms of Microstructure - Hafni Hafni; Karnova Yanel (Jurnal Teknik Mesin (JTM), 2018)
The flaws or failures that occur in the welding results can be caused by many things, one caused by the quality of the electrode. The quality of the electrode may be affected by moisture caused by water or oil, thereby damaging the flux lining the electrode. To know how big influence of oil on electrode to result of welding of low carbon steel hence conducted a research by using oil as element of elektrodanya moisturizer. The humidity of the electrode is carried out by immersing the electrodes into the SAE 40 oil oil until it reaches the absorption of 5% by weight of the electrode. Welding process is then performed on low carbon steel plate with DCSP polarity.The result of welding is metallographic testing to observe macrostructure and microstructure of welding area and base metal. From the test results obtained that the moisture of electrodes by oil cause defects in the weld metal region on the low carbon steel welding results.